A core epiphytic bacterial consortia synergistically protect citrus from postharvest disease. (1st May 2023) - Jing, Jiayi; Wang, Wenjun; Deng, Lili; Yi, Lanhua; Zeng, Kaifang
Highlights: According to different criteria, 24 genera were defined as core members. Core bacteria tend to be beneficial, while fungi were the opposite. 115 bacterial strains were cultured and identified. 8 strains were selected to construct the synthetic community. The synthetic community could control the citrus postharvest disease. Abstract: Biological antagonists are a series of microbes that can control pathogens to reduce the incidence of disease or reduce symptoms. Herein, four varieties of citrus fruit were selected to perform an amplicon sequencing on their epiphytic microbiota to get a systematic understanding of them. Co-occurrence network, Venn, and LefSe analysis were performed to filter to 24 genera which represent the universality, specificity, and correlation among samples. Functional analysis hinted that the genes related to chitinase, which most of these 24 bacteria carry, might lead to a disease-suppressive phenotype. 115 strains of epiphytic bacteria were isolated, and the bacterial synthetic community was constructed by 8 strains. The in vivo test results indicated they were able to reduce pathogen development for a longer time than separate inoculation. Collectively, this study showed the disease control potential provided by native epiphytic bacteria of fruit and give a new strategy to sustainable agriculture.